The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1080/15428119691014215
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Hazards from Lead Shielding

Abstract: Uncoated metallic lead is widely used as radiation shielding in research and development, nuclear medicine and radiology, and various manufacturing processes. The common use of lead shielding, however, may present an insidious health hazard due to lead dust. Field and laboratory measurements were collected to evaluate the distribution and removal of lead from radiation shielding material as well as to measure airborne exposures during large shielding emplacement projects. The data indicate that lead is readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Given that lead is an important shielding material for g-and x-rays, it is generally not feasible to eliminate or substitute it. Therefore, other means must be used to minimize health hazards from dispersible lead (2). Most lead contamination found within the patient areas was around areas that contained lead shielding.…”
Section: Discussionmentioning
confidence: 99%
“…Given that lead is an important shielding material for g-and x-rays, it is generally not feasible to eliminate or substitute it. Therefore, other means must be used to minimize health hazards from dispersible lead (2). Most lead contamination found within the patient areas was around areas that contained lead shielding.…”
Section: Discussionmentioning
confidence: 99%
“…These materials find application in personal protective equipment (PPE), protective panels, and screens to reduce x‐ray exposure in different industries, including biomedical, space, and nuclear sectors. Indeed, the current use of x‐ray protective materials increases workers' exposure to lead, which poses severe health consequences due to the presence of lead dust in the work environmenxts, often resulting from the deterioration of shielding elements 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the current use of x-ray protective materials increases workers' exposure to lead, which poses severe health consequences due to the presence of lead dust in the work environmenxts, often resulting from the deterioration of shielding elements. 1,2 As materials with high mass density (ρ) and containing high atomic number (Z) elements are intrinsically effective for x-ray shielding, 3,4 various multiphase systems containing elements with a high atomic number, such as barium, tungsten, and bismuth, have been investigated for radioprotective purposes to substitute lead, which are often included in compounds with low lead content. 5 Another limitation of conventional lead shielding is its inherent blind spot within the energy range of 70-90 keV.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the deposition of Pb dust from uncoated Pb-shields on surfaces such as human skins, clothes and floors. Moreover, such Pb dusts can be remained in air where it maybe accidentally ingested and inhaled [10][11][12][13]. These pathways are significant sources of Pb exposures to medical workers and patients [11,12].…”
Section: Introductionmentioning
confidence: 99%